Assessment of sperm acrosome status, malondialdehyde and aspartate aminotransferase enzyme concentration of frozen semen from Limousin and Simmental bulls in different commercial diluents - Muhammad Agus Tahar; Komariah Komariah; Henny Nuraini; Tulus Maulana; Muhammad Gunawan; R Iis Arifiantini (Jurnal Ilmu Ternak dan Veteriner, 2022)
Sperm cryopreservation is the process of preserving sperm cells at low temperatures, so that its frozen semen can be used in the future. The quality of the frozen sperm is affected by the diluent. The objective of this study was to compare the effects of commercial diluents on acrosome status, malondialdehyde (MDA) and aspartate aminotransferase (AspAT) enzyme concentration of thawed Limousin and Simmental bull semen. Semen was collected twice weekly using an artificial vagina. The fresh semen processed into frozen semen had  sperm motility of 70%. The one-step procedure was used for the dilution methods. Andromed®, Optixcell® and Steridyl® were used as diluents. Data were analyzed by analysis of variance (ANOVA) followed by Tukey HSD 5% confidence interval. The result showed no interaction (P0.05) between two factors on acrosome status. The sperm acrosome damage of Simmental in Steridyl® was significantly lower than others (P0.05), although all diluents showed low sperm acrosome damage. Also, no interaction between the type of diluent and breed on MDA and AspAT enzyme concentrations was detected (P0.05). The results suggest that three commercial diluents have equal efficacy in protecting acrosome status and maintaining MDA and AspAT enzyme concentrations of frozen Limousin and Simmental bull semen. Therefore, all commercial diluents can be an alternative for Limousin and Simmental frozen semen.